Assessing the Effectiveness of Gender Quotas in Indonesia’s Electoral System - Jessica Virgoria Septiana; Nourma Dewi; Yulian Dwi Nurwanti (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2026)
Women’s representation in legislative elections constitutes a critical indicator of an inclusive and equitable democracy; however, its realization in Indonesia remains suboptimal. This study aims to examine the implementation of regulatory provisions on women’s representation and to identify the key factors contributing to its limited attainment from a constitutional law perspective. The research employs a normative juridical approach, complemented by empirical insights derived from a review of secondary data and relevant literature. The findings reveal that, although affirmative action policies are supported by a robust legal framework, their implementation continues to encounter structural, cultural, and institutional constraints. The persistently low level of women’s representation is influenced by weak enforcement mechanisms, the dominance of party elites, features of the electoral system, and entrenched patriarchal norms. This study concludes that strengthening regulatory frameworks and advancing political reform are essential to achieving substantive women’s representation.